Suhu dan Lama Penyimpanan Plasma Sitrat Berdampak Terhadap Activated Partial Thromboplastin Time - Ningsih, Agita Fortuna Septa; Handayati, Anik; Arifin, Syamsul (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Prothrombin Time (PT) and activated Partial Thromboplastin Time (aPTT) examinations are routine coagulation examination parameters that are useful for determining the ability of the blood clotting mechanism in the body. In PT and aPTT examinations, the pre-analytical stage is very important to obtain valid examination results including in terms of temperature and duration of sample storage. The purpose of this study was to analyze the effect of temperature and duration of citrate plasma sample storage on PT and aPTT examination results. This study was conducted using ten blood samples from normal individuals. The samples studied were citrate plasma stored at refrigerator and freezer temperatures for 24 hours and 48 hours, then the results were compared with direct examination to see the effect of temperature and storage duration on PT and aPTT examinations. The results of the analysis showed that storing citrate plasma at refrigerator and freezer temperatures for 24 hours and 48 hours did not significantly affect PT examinations and significantly affected aPTT examinations. The aPTT value extended by about 3 to 4 seconds after the sample was stored for 24 hours and 48 hours at refrigerator temperature. Meanwhile, in freezer temperature storage, the aPTT value extends about 1 to 2 seconds after 24 hours and 48 hours. This study concluded that temperature and duration of citrate plasma storage affect the results of aPTT examination.Keywords: prothrombin time; activated partial thromboplastin time; coagulation examination; temperature; storage durationABSTRAK Pemeriksaan Prothrombin Time (PT) dan activated Partial Thromboplastin Time (aPTT) merupakan parameter pemeriksaan koagulasi rutin yang berguna untuk mengetahui kemampuan mekanisme pembekuan darah dalam tubuh. Pada pemeriksaan PT dan aPTT, tahap pre-analitik menjadi sangat penting untuk mendapat hasil pemeriksaan yang valid termasuk dalam hal suhu dan lama waktu penyimpanan sampel. Tujuan dari penelitian ini adalah menganalisis pengaruh suhu dan lama penyimpanan sampel plasma sitrat terhadap hasil pemeriksaan PT dan aPTT. Penelitian ini dilakukan menggunakan sepuluh sampel darah dari individu normal. Sampel yang diteliti adalah plasma sitrat yang disimpan pada suhu refrigerator dan suhu freezer selama 24 jam dan 48 jam kemudian hasilnya dibandingkan dengan pemeriksaan langsung untuk melihat pengaruh suhu dan waktu simpan terhadap pemeriksaan PT dan aPTT. Hasilnya analisis menunjukkan bahwa  penyimpanan plasma sitrat pada suhu refrigerator dan freezer selama 24 jam dan 48 jam tidak berpengaruh terhadap pemeriksaan PT secara signifikan dan berpengaruh signifikan pada pemeriksaan aPTT. Nilai aPTT memanjang sekitar 3 sampai 4 detik setelah sampel disimpan selama 24 jam dan 48 jam pada suhu refrigerator. Sedangkan pada penyimpanan suhu freezer, nilai aPTT memanjang sekitar 1 sampai 2 detik setelah 24 jam dan 48 jam. Penelitian ini menyimpulkan bahwa suhu dan lama penyimpanan plasma sitrat berpengaruh terhadap hasil pemeriksaan aPTT.Kata kunci: prothrombin time; activated partial thromboplastin time; pemeriksaan koagulasi; suhu; waktu penyimpanan